PENERAPAN EVALUASI PEMBELAJARAN AL-QUR’AN METODE TILAWATI DI MTs DARUL AMIN PALANGKA RAYA - Rahmadianti, Erisma; Khalfiah, Yuliani; Afifah, Neela (CV. Lafadz Jaya, 2025)
This study aims to describe the forms of evaluation used in the Tilawati method for Qur’anic reading activities among students at MTs Darul Amin Palangka Raya. The research employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The findings indicate that the learning evaluation is carried out periodically after the completion of each Tilawati level (jilid), covering indicators such as reading fluency, tajwid accuracy, and articulation of letters (makharijul huruf), which are structured in both formative and summative formats. Furthermore, the evaluation has proven to be effective in tracking students’ Qur’anic reading proficiency due to its in-depth and comprehensive assessment approach, enabling the identification of each student’s individual capabilities.